2003
DOI: 10.1111/j.1349-7006.2003.tb01372.x
|View full text |Cite
|
Sign up to set email alerts
|

Up‐regulation of DNA‐dependent protein kinase correlates with radiation resistance in oral squamous cell carcinoma

Abstract: DNA-PK is a nuclear protein with serine/threonine kinase activity and forms a complex consisting of the DNA-PKcs and a heterodimer of Ku70 and Ku80 proteins. Recent laboratory experiments have demonstrated that the DNA-PK complex formation is one of the major pathways by which mammalian cells respond to DNA double-strand breaks induced by ionizing radiation. In this study, we evaluated the relationship between expression levels of DNA-PKcs, Ku70 and Ku80 proteins and radiation sensitivity in oral squamous cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
78
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(89 citation statements)
references
References 22 publications
11
78
0
Order By: Relevance
“…An increased expression of DNA-PKcs and Ku70 was observed in residual tumour, whereas the percentage of the Ku80-positive cells was similar in tumour tissue pre-and post RT. The results reported by Shintani et al (2003) are partly in accordance with ours, suggesting that upregulation of DNA-PKcs and Ku70 associates with radioresistance. However, the discrepancy with respect to Ku80 between the studies is not clearly understood but may be related to differences in treatment type, intracavitary vs EBRT, or to the effect of chemotherapy, which was given to half of Prior RT After RT Figure 1 (A -C) Positive immunohistochemical staining of Ku70 (A) in poorly differentiated squamous cell carcinoma, Ku86 (B) in glassy cell adenocarcinoma and p21 (C) in moderately differentiated adenocarcinoma of the cervix.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…An increased expression of DNA-PKcs and Ku70 was observed in residual tumour, whereas the percentage of the Ku80-positive cells was similar in tumour tissue pre-and post RT. The results reported by Shintani et al (2003) are partly in accordance with ours, suggesting that upregulation of DNA-PKcs and Ku70 associates with radioresistance. However, the discrepancy with respect to Ku80 between the studies is not clearly understood but may be related to differences in treatment type, intracavitary vs EBRT, or to the effect of chemotherapy, which was given to half of Prior RT After RT Figure 1 (A -C) Positive immunohistochemical staining of Ku70 (A) in poorly differentiated squamous cell carcinoma, Ku86 (B) in glassy cell adenocarcinoma and p21 (C) in moderately differentiated adenocarcinoma of the cervix.…”
Section: Discussionsupporting
confidence: 81%
“…the patients in the study of Shintani et al (2003) Moreover, differences in tumour type as well as in the time span between end of RT and surgery may contribute. Several studies have been performed with the aim of identifying molecular markers that could predict RT response in cervical cancer (Fyles et al, 1998;Haensgen et al, 2001;Lee et al, 2005;Kim et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…DNA-PK may also play a vital role in cellular responses to low amounts of radiation-induced damage (Vaganay-Juery et al, 2000;Marples et al, 2002), which make it an attractive molecular target. This is especially true given that several studies have reported that components of the DNA-PK complex are upregulated in cancer cells (Sirzen et al, 1999;Wilson et al, 2000;Zhao et al, 2000;Shintani et al, 2003). Radiation remains a highly effective means to target human tumor-specific death.…”
Section: The Death Of Dna-pkmentioning
confidence: 95%
“…32 In glioma specimens, hyperactivity of this protein was associated with tumor grading 33 and radio-resistance, 34 and its up-regulation after radiation treatment has been associated with radio-resistance in recurrent oral squamous cell carcinomas. 35 Using a DNA-PK kinase assay and assessing the phosphorylation status of replication protein A 2, a previous study demonstrated IR-induced DNA-PK activity in glioblastoma cell lines. 36 This increased activity was correlated with the survival fraction of those cells after a 5-Gy dose of irradiation, which suggests the role of DNA-PK in radiation resistance.…”
Section: Discussionmentioning
confidence: 99%